2022
DOI: 10.1002/anie.202208475
|View full text |Cite
|
Sign up to set email alerts
|

Small‐Molecular‐Weight Additives Modulate Calcification by Interacting with Prenucleation Clusters on the Molecular Level**

Abstract: Small-molecular-weight (MW) additives can strongly impact amorphous calcium carbonate (ACC), playing an elusive role in biogenic, geologic, and industrial calcification. Here, we present molecular mechanisms by which these additives regulate stability and composition of both CaCO 3 solutions and solid ACC. Potent antiscalants inhibit ACC precipitation by interacting with prenucleation clusters (PNCs); they specifically trigger and integrate into PNCs or feed PNC growth actively. Only PNC-interacting additives … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…Our data therefore suggest that surface embedment of SHMP during the initial dissolution−recrystallization of aragonite and calcite yields surfaces where the thermodynamic forces that drive the aragonite-to-calcite pump no longer prevail. This mode of action of P-species embedment is consistent with our earlier study 14 that identified that strong phosphate•••carbonate interactions (Ca 2+ -mediated) impeded CaCO 3 nucleation in solution, and their persistence in the amorphous calcium carbonate (ACC) solid also prevented its crystallization. 13 Aragonite-to-calcite conversion in aqueous environments is a widespread phenomenon.…”
Section: Journal Of the American Chemical Societysupporting
confidence: 91%
“…Our data therefore suggest that surface embedment of SHMP during the initial dissolution−recrystallization of aragonite and calcite yields surfaces where the thermodynamic forces that drive the aragonite-to-calcite pump no longer prevail. This mode of action of P-species embedment is consistent with our earlier study 14 that identified that strong phosphate•••carbonate interactions (Ca 2+ -mediated) impeded CaCO 3 nucleation in solution, and their persistence in the amorphous calcium carbonate (ACC) solid also prevented its crystallization. 13 Aragonite-to-calcite conversion in aqueous environments is a widespread phenomenon.…”
Section: Journal Of the American Chemical Societysupporting
confidence: 91%
“…Apart from the interface model discussed in the present work, current studies aim at the pH-dependent characterization of prenucleation species and their interplay with antiscalant additives. [32]…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, solute‐rich domains featuring poly‐ionic chains that exchange ion‐ion and ion‐water contacts on the 10 ps scale appear as the key field of application of the presented method. Apart from the interface model discussed in the present work, current studies aim at the pH‐dependent characterization of prenucleation species and their interplay with antiscalant additives [32] …”
Section: Discussionmentioning
confidence: 99%
“…They found that the remaining additives did not inhibit nucleation, but they could form polycrystals by preferentially adsorbing to cluster-related structures. Recently, Duchstein et al 53 investigated the regulation of mineralization by small molecular weight additives at the molecular level by interacting with prenucleated clusters. Amorphous calcium carbonate (ACC) is a transient precursor of crystalline calcium carbonate, so the production of crystalline calcium carbonate can be prevented if ACC can be stabilized.…”
Section: Methodologies and Strategies For Crystallization Inhibitionmentioning
confidence: 99%